Investigation of the effect of the efficiency of noise at different intensities on the DNA of the newborns - Nesrin Ceylan; Sultan Kaba; Kamuran Karaman; Metin Celiker; Yildiray Basbugan; Nihat Demir (Noise and Health, 2016)
Hearing loss can occur in newborns exposed to high-level noise; noise exposure can cause more physiological stress and can lead to DNA damage. This study was designed to determine DNA damage in newborn rats exposed to sound at different concentrations. For this purpose, 28 newborn (3-6 days old) rats were divided into four groups of 7 rats in each group (Control and Groups of 40 decibel (dB), 70 dB, and 110 dB]. In the experimental groups, 40 dB, 70 dB, and 110 dB (7.5-15 kHz) of sound was applied to the experimental groups for 30 min a day for 7 days. DNA damage levels in the serums obtained from this study were determined by the enzyme-linked immunosorbent assay (ELISA) method. According to this, it was determined that DNA damage in the group exposed to 110 dB showed a statistically significant increase (P < 0.05) compared to the compared to the control, 40 dB, and 70 dB groups. Related to the subject, it was concluded that DNA damage may occur in newborns exposed to 110 dB or higher sound in neonatal units, wards, and home environments with newborn babies. Mothers should be warned about this situation and noise should be kept under 110 dB volume in the environments with the newborns.